An Approach of Vector Autoregression Model for Inflation Analysis in Indonesia - Idah Zuhroh; Hendra Kusuma; Syela Kurniawati (Journal of Economics, Business, and Accountancy Ventura, 2017)
A control of the inflation rate caused by the fluctuations in foreign exchange reserves, money supply, and exchange rate is required to create the stability of the country's economy. This study aims to analyze the dynamic impact of disturbance factors contained in the variables of foreign exchange reserves, the money supply, and the exchange rate. This research used monthly data from June 2009 to November 2016. It used a method used of Vector Autoregression. The result shows that a foreign exchange reserve has a negative relationship nut not significant effect on inflation, money supply has positive relationship and significant effect on inflation, and exchange rate of rupiah to US dollar has negative relationship and significant effect on inflation. The responce of inflation from shocking occurs to supply, foreign exchange reserves and exchange rate tend to be convergent and the biggest contribution that influences inflation the most is exchange rate beside inflation itself.